Current Developments in Biotechnology and Bioengineering : Production, Isolation and Purification of Industrial Products - Pandey, Ashok editor 211219; Sangeeta Negi editor 631948; Soccol, Carlos Ricardo, editor; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2017)
Current Developments in Biotechnology and Bioengineering: Production, Isolation and Purification of Industrial Products provides extensive coverage of new developments, state-of-the-art technologies, and potential future trends, focusing on industrial biotechnology and bioengineering practices for the production of industrial products, such as enzymes, organic acids, biopolymers, and biosurfactants, and the processes for isolating and purifying them from a production medium.